Research on Impact Process of Lander Footpad against Simulant Lunar Soils - Bo Huang; Zhujin Jiang; Peng Lin; Daosheng Ling (Shock and Vibration)
The safe landing of a Moon lander and the performance of the precise instruments it carries may be affected by too heavy impact on touchdown. Accordingly, landing characteristics have become an important research focus. Described in this paper are model tests carried out using simulated lunar soils of different relative densities (called “simulant” lunar soils below), with a scale reduction factor of 1/6 to consider the relative gravities of the Earth and Moon. In the model tests, the lander was simplified as an impact column with a saucer-shaped footpad with various impact landing masses and velocities. Based on the test results, the relationships between the footpad peak feature responses and impact kinetic energy have been analyzed. Numerical simulation analyses were also conducted to simulate the vertical impact process. A 3D dynamic finite element model was built for which the material parameters were obtained from laboratory test data. When compared with the model tests, the numerical model proved able to effectively simulate the dynamic characteristics of the axial forces, accelerations, and penetration depths of the impact column during landing. This numerical model can be further used as required for simulating oblique landing impacts.